PENGARUH ASET PAJAK TANGGUHAN DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI DI BURSA EFEK INDONESIA - Simarmata, Brigitta; Saragih, Joana L (Jurnal Ilmiah Akuntansi (JIMAT), 2022)
This study aims to determine and empirically prove the effect of Deferred Tax Assets and Deferred Tax Expense on Earnings Management. The population in this study are all financial statements of infrastructure, utility and transportation companies listed on the Indonesia Stock Exchange in 2015-2017. The sample in this study was obtained by purposive sampling, with a sample of 18 companies. Data collection techniques using documentation techniques. The data analysis technique used is multiple linear regression and hypothesis testing using t test and f test with a significance level of 5%. The results of this study indicate that the partial test (t test): (1) deferred tax assets have a negative and insignificant effect on earnings management, this is evidenced by the t test where the deferred tax assets have a t count > t table (-1.060<1 .67356) with a significant level of 0.294 > 0.05. Which means that the deferred tax assets carried out do not guarantee earnings management by the Indonesia Stock Exchange company. Which means that the magnitude of the change in deferred tax expense can guarantee the enactment of earnings management actions by companies on the Indonesia Stock Exchange. The results of the simultaneous test (F test) of deferred tax assets and deferred tax expense are positive and significant on earnings management.